Autologous wound margin point columnar full‐thickness skin grafting combined with negative pressure wound therapy improves wound healing in refractory diabetic foot ulcers. Issue 5 (28th October 2022) - Mo, Jianming; Huang, Yuanjing; Wang, Qiu; Zhong, Hua; Zhai, Zhenwei; Nong, Yuechou; Yan, Xiaodong; Huang, Xiulu; Huang, Jianhao; Yang, Suping; Sun, Jingxia; Han, Jiaxia; et al.
Abstract: Diabetic lower extremity ulcers (DLEUs) are a severe complication of diabetes mellitus (DM) and are difficult to heal. This study aimed to explore the efficacy of autologous point columnar full‐thickness skin graft taken from the ulcer wound margin combined with negative pressure wound therapy (NPWT) in refractory DLEUs. This is a prospective cohort study. A total of 40 inpatients with refractory DLEUs were recruited in the Diabetes Foot Center of Guangxi Zhuang Autonomous Region People's Hospital from October 2019 to November 2021. According to the doctors' professional suggestions and the patients' personal wishes, these enrolled patients were divided into two groups based on different topical wound management: the graft group ( n = 18) and the conventional wound therapeutic (CWT) group ( n = 22). The efficacy evaluations included the time to complete re‐epithelialization of the wound and healing speed within 14 days of graft treatment or after 14 days of graft treatment in the two groups. Before the treatment, the graft group had a significantly larger ulcer area than the CWT group [27.22 (15.28, 46.59) versus 10.92 (7.00, 24.93) cm 2, P < .01]. However, the time to complete wound re‐epithelialization in the graft group was shorter than in the CWT group [58.22 ± 30.60 versus 86.09 ± 49.54 d, P < .05]. Meanwhile, the healing speed in graft group was markedly faster than in CWT group, whether within 14 days [0.60 (0.40, 0.92) versus 0.16 (0.07, 0.34) cm 2 /d, P < .01] or after 14 days of graft treatment [0.57 (0.45, 0.91) versus 0.13 (0.08, 0.27) cm 2 /d, P < .01]. However, the total treatment cost in the graft group was lower than in the CWT group [419.59 ± 137.20 versus 663.97 ± 497.02 , P < .05]. The novel treatment modality of autologous full‐thickness skin graft taken from the ulcer wound margin combined with NPWT has hereby proposed for the first time, and is a safe, effective, and reliable method with a good performance‐to‐cost ratio to promote wound healing and shorten the healing time for DLEUs.